Vzpostavljanje omrežja Natura 2000 - Petkovšek, Matej (Varstvo narave, 2015)
The increased nature conservation awareness in the second half of the 20th century initiated nature conservation movements and founding of international nature conservation organizations. Various international conventions were adopted, aimed at biodiversity conservation. In order to achieve these objectives, the EU adopted the Birds and Habitats Directives. The article describes the designation of Natura 2000 network on the basis of both European directives. The procedure of designating the Natura 2000 sites in Slovenia, including biogeographic seminars, is described in detail. The data on changes in the Decree on special protection areas (Natura 2000 sites) that concern the number and surface area of Natura 2000 sites as well as the number of qualifying species and habitat types within the sites are gathered herewith.
Keywords: biogeografski seminar; Direktiva o habitatih; Direktiva o pticah; določitev omrežja; Natura 2000